SEXISM AND GENDER CONSTRUCTS IN THE NOVEL TUHAN IZINKAN AKU MENJADI PELACUR: A CRITICAL DISCOURSE ANALYSIS - Hasbi, Nur; Mardatillah, Rahmi; Neyarasmi, Fadilah (JURNAL KONFIKS, 2025)
This study examines acts of sexism in the novel Tuhan Ijinkan Aku Menjadi Pelacur through a qualitative approach using critical discourse analysis. Data collection was carried out through documentation studies. The data were then analyzed through three stages, namely description, interpretation, and explanation. This study focuses on textual excerpts that contain sexist elements against men and women. Through a critical discourse analysis approach, the novel Tuhan Ijinkan Aku Menjadi Pelacur by Muhidin M. Dahlan reveals how language and narrative are used to reproduce, challenge, and deconstruct male power over women and female power over men in society. The research findings reveal two main forms of sexism in the novel. First, sexism against men is depicted through gender stereotypes that depict men as strong, responsible, and the main breadwinners for the family. In addition, men in the novel experience various forms of violence and sexual harassment, including physical violence and verbal abuse. This depiction reinforces rigid gender expectations that limit male identity to certain roles and behaviors. Second, sexism against women is manifested through stereotypes that impose expectations of nurturing, obedience, and moral purity. Women are subjected to acts of violence and sexual harassment, reflecting the broader social injustices they face. The novel illustrates how gender constructs contribute to oppression and inequality. Through its narrative, Tuhan Izinkan Aku Menjadi Pelacur presents sexism as a multidimensional issue that affects both genders. A critical discourse analysis of the novel reveals that the work not only presents the personal narratives of a woman and a man, but also serves as a tool for social critique that challenges gender constructs and sexism that are deeply rooted in society. The novel encourages readers to reflect on and question social and religious norms that have been accepted uncritically, and advocates for the importance of gender equality and individual freedom.